2020
DOI: 10.1155/2020/7197054
|View full text |Cite
|
Sign up to set email alerts
|

Using the Atherogenic Index of Plasma to Estimate the Prevalence of Ischemic Stroke within a General Population in a Rural Area of China

Abstract: Objective. To investigate the relationship between the atherogenic index of plasma (AIP) and ischemic stroke. Design. We collected a range of data from 11,495 residents (aged ≥35 years; 54.28% female) residing in rural areas of northeast China between January and August 2013, including fasting lipid profile and anthropometric parameters. Logistic regression models were used to evaluate the correlation between AIP and ischemic stroke. Category-free analysis was used to determine whether AIP enhanced our capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
0
18
0
1
Order By: Relevance
“…A positive association between AIP and CVDs has already been observed in different populations, such as postmenopausal women and staff [19,30]. Moreover, AIP is positively associated with non-alcoholic fatty liver disease (NAFLD), advanced subclinical coronary artery disease (CAD), ischemic stroke, atherosclerosis, MetS, and obesity; and is a useful and reliable marker for predicting these diseases [29,[31][32][33][34]. Results of a study on Malaysian population showed that among lipid profile indices, AIP was more positively correlated with TG and was more negatively correlated with HDL-C, thus AIP was considered to be the strongest marker in predicting risk of CVDs among the other indices [30].…”
Section: Discussionmentioning
confidence: 99%
“…A positive association between AIP and CVDs has already been observed in different populations, such as postmenopausal women and staff [19,30]. Moreover, AIP is positively associated with non-alcoholic fatty liver disease (NAFLD), advanced subclinical coronary artery disease (CAD), ischemic stroke, atherosclerosis, MetS, and obesity; and is a useful and reliable marker for predicting these diseases [29,[31][32][33][34]. Results of a study on Malaysian population showed that among lipid profile indices, AIP was more positively correlated with TG and was more negatively correlated with HDL-C, thus AIP was considered to be the strongest marker in predicting risk of CVDs among the other indices [30].…”
Section: Discussionmentioning
confidence: 99%
“…A multistage, stratified, random cluster sampling was used. The full details of the design and principles of the study were described elsewhere [ 17 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…In China, IS is the most prevalent type of cerebrovascular event. Therefore, the prevention of IS is an important and urgent public health issue [ 6 , 7 , 32 ]. Since the discovery of the association of Hcy with the pathogenesis of atherosclerosis, Hcy-lowering therapies have attracted considerable attention among the various prevention strategies for IS [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Researches have demonstrated that ischemic stroke (IS) is the most prevalent stroke subtype in China, accounting for about 70-86% of all strokes [ 2 , 5 ]. Therefore, early identification and management of associated risk factors are critical measures to prevent and treat the first IS [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%